1983
DOI: 10.1002/j.1460-2075.1983.tb01424.x
|View full text |Cite
|
Sign up to set email alerts
|

A cellular protein phosphorylated by the avian sarcoma virus transforming gene product is associated with ribonucleoprotein particles.

Abstract: In chick embryo fibroblasts transformed by Rous sarcoma virus (RSV) the tyrosine phosphorylation of a cellular protein of 34,000 daltons mol. wt. (34 kd) is greatly enhanced; this was shown to be catalyzed by the phosphotransferase activity of RSV transforming protein pp60src. We report here that in cytoplasmic extracts of both normal and transformed cells, in the presence of magnesium ions, the majority of the 34‐kd protein is associated with large structures and that a fraction of 34 kd appears to be associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 30 publications
5
31
0
Order By: Relevance
“…69 One study reported that 15% of cellular ANXA2 was nuclear and was released from the nucleus by RNase A. 74,76,77 This is consistent with the report that ANXA2 binds to RNA 78 ; nevertheless, the role of nuclear ANXA2 still remains elusive.The tissue content of ANXA2 and S100A10 has been reported in both avian and mammalian tissues. These proteins are undetectable in heart, smooth muscle, skeletal muscle, and cartilage.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…69 One study reported that 15% of cellular ANXA2 was nuclear and was released from the nucleus by RNase A. 74,76,77 This is consistent with the report that ANXA2 binds to RNA 78 ; nevertheless, the role of nuclear ANXA2 still remains elusive.The tissue content of ANXA2 and S100A10 has been reported in both avian and mammalian tissues. These proteins are undetectable in heart, smooth muscle, skeletal muscle, and cartilage.…”
supporting
confidence: 70%
“…[50][51][52] ANXA2 is primarily localized in the cytoplasm and plasma membrane with a small population in the nucleus. 74 Many functions have been attributed to ANXA2. Extracellular ANXA2 was originally identified as a receptor for tenascin-C, 75 and The convex side faces the cellular membrane and contains the Ca 2ϩ and phospholipid binding sites, whereas the concave side faces away from the membrane and contains both the N-and C-terminal regions of ANXA2.…”
Section: The Aiit Structurementioning
confidence: 99%
“…It has become evident from cell fractionation, morphologic and immunochemical studies that p36, or at least a fraction of it, is closely associated with plasma membranes (Cooper and Hunter, 1982;Amini and Kaji, 1983;Courtneidge et al, 1983;Nigg et al, 1983), with detergent-resistant cytoskeletal structures (Cheng and Chen, 1981;Cooper and Hunter, 1982) or, according to one study, with ribonucleoprotein particles (Arrigo et al, 1983). However, distinctly specific interactions, such as that of vinculin, another important tyrosine kinase substrate, and focal adhesion sites (Sefton et al, 1981), have not been found between p36 and other membrane or cytoskeletal components.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that ANXA2 immunoprecipitated from UV-irradiated cultured cells associated with RNA and formed a RNA-ANXA2 cross-linked ribonucleoprotein complex. These authors also showed by biochemical fractionation experiments that about 10 -15% of the total cellular ANXA2 was associated with the nucleus (31). Ensuing studies showed that ANXA2 could bind to deoxyribonucleic acid structures such as Z-DNA (32) or Alu subsequences (33).…”
mentioning
confidence: 93%